Human antibodies to the dengue virus E-dimer epitope have therapeutic activity against Zika virus infection - Fernandez, E; Dejnirattisai, W; Cao, B; Scheaffer, SM; Supasa, P; Wongwiwat, W; Esakky, P; Drury, A; Mongkolsapaya, J; Moley, KH; Mysorekar, IU; Screaton, GR; et al. (Springer Nature, 2017)
The Zika virus (ZIKV) epidemic has resulted in congenital abnormalities in fetuses and neonates. Although some cross-reactive dengue virus (DENV)-specific antibodies can enhance ZIKV infection in mice, those recognizing the DENV E-dimer epitope (EDE) can neutralize ZIKV infection in cell culture. We evaluated the therapeutic activity of human monoclonal antibodies to DENV EDE for their ability to control ZIKV infection in the brains, testes, placentas, and fetuses of mice. A single dose of the EDE1-B10 antibody given 3 d after ZIKV infection protected against lethality, reduced ZIKV levels in brains and testes, and preserved sperm counts. In pregnant mice, wild-type or engineered LALA variants of EDE1-B10, which cannot engage Fcg receptors, diminished ZIKV burden in maternal and fetal tissues, and protected against fetal demise. Because neutralizing antibodies to EDE have therapeutic potential against ZIKV, in addition to their established inhibitory effects against DENV, it may be possible to develop therapies that control disease caused by both viruses.